Estudio molecular del gen de la enfermedad de von Hippel-Lindau (VHL) : detección de portadores y caracterización funcional de nuevas variantes génicas - Mathó Pacielo, Cecilia (2016)
von Hippel-Lindau disease is an autosomal dominant cancer syndrome caused by mutations in the VHL tumor suppressor gene. VHL protein (pVHL) forms a complex (VBC) with Elongins B-C, Cullin2 and Rbx1. Although other functions have been discovered, the most described function of pVHL is to recognize and target hypoxia inducible factor (HIF) for degradation. This thesis comprises the implementation of the analysis of large deletions, to enable the complete study of the gene, and the functional characterization of two novel variants of the gene by in vitro, in vivo and in silico approaches.\nOur results underline the importance of the complete genetic study of the VHL gene for the confirmation of von Hippel-Lindau disease, not only in patients with clinical diagnostic criteria, but also in those patients presenting a single typical manifestation, enabling their correct diagnosis and follow-up. Based on the in vitro, in vivo and in silico studies, we have demonstrated the pathogenicity of P138R and L163R novel variants, involving HIF dependent and HIF independent mechanisms. These results provide the basis for future studies regarding the impact of structural alterations on post translational modifications that drive pVHL?s fate and functions.